Aplicação de um algoritmo de evolução diferencial para análise de pentes de frequências óticas gerados com moduladores Mach-Zehnder - Pendiuk, Guilherme Francisco Iakmiu (2019)
This work presents the development of an algorithm based on Differential Evolution, which is capable of identifying parameters of electrical signals applied to Mach-Zehnder modulators with the objective of producing flat optical frequency combs. Simulations with three different setup configurations are investigated: with only one modulator, with two modulators in series, and with two modulators in parallel. Also, some simulations results are used in experiments for comparison between ideal and real cases. The results show that the algorithm is useful for optical frequency comb generation capability analysis, but some compensations should be made in order to utilize the algorithm results in practical systems.